Grace, Lulabelle, and Alice, volunteer recognition banquet, June 7, 1990
The caption on back reads, 'Grace, Lulabelle, and Alice Volunteer Recognition Banquet, 6-7-90'. On the left, Grace is wearing a white sweater with a white hat and holding a light brown cane. In the middle of the photo, Lulabelle is wearing a white shirt with a Red dress suit over it. In their jacket pocket, there are some white flowers and has a name tag. Alice, on the right, is wearing a black dress suit with a colorful neck scarf, holding a clipboard in their left hand. In front of them, there is a table with a basket, two wine glasses filled with water, and a food takeout box.